Liposome-Encapsulated Bioactive Guttiferone E Exhibits Anti-Inflammatory Effect in Lipopolysaccharide-Stimulated MH-S Macrophages and Cytotoxicity against Human Cancer Cells. (30th August 2022) - Dzoyem, Jean Paul; Pinnapireddy, Shashank Reddy; Fouotsa, Hugues; Brüßler, Jana; Runkel, Frank; Bakowsky, Udo
Abstract : Background . Guttiferone E is a naturally occurring polyisoprenylated benzophenone exhibiting a wide range of remarkable biological activities. But its therapeutic application is still limited due to its poor water solubility. This study is aimed at preparing guttiferone E-loaded liposomes and assessing their in vitro cytotoxicity and anti-inflammatory effect. Methods . Liposomes containing guttiferone E were prepared by the thin film hydration method, and the physicochemical characteristics were determined using dynamic light scattering, laser Doppler velocimetry, and atomic force microscopy. The cytotoxicity was assessed by the MTT assay. The fluorometric cyclooxygenase (COX) activity assay kit was used to assess the COX activity while the nitric oxide production was evaluated by the Griess reagent method. Results . The liposomes with a mean size of 183.33 ± 17.28   nm were obtained with an entrapment efficiency of 63.86%. Guttiferone E-loaded liposomes successfully decreased the viability of cancer cells. The overall IC50 values varied between 5.46  μ g/mL and 22.25  μ g/mL. Compared to the untreated control, guttiferone E-loaded liposomes significantly reduced the nitric oxide production and the activity of COX in a concentration-dependent manner. Conclusion . This study indicates that liposomes can be an alternative to overcome the water insolubility issue of the bioactive guttiferone E.